Measurement and Correlation of Solid-Liquid Equilibria of Phenyl Salicylate with C4 Alcohols - 魏东炜 裴艳红 张超 闫峰 (Chinese journal of chemical engineering, 2009)
In an equilibrium vessel, the solid-liquid equilibria （SLE） for three binary mixtures of phenyl salicylate with 1-butanol, 2-butanol, and 2-methyl-1-propanol, respectively, have been measured from 283.15 K to the melting temperature of the solute using a method in which an excess amount of solute was equilibrated with the alcohol solution. The liquid concentrations of the investigated phenyl salicylate in the saturated solution were analyzed by UV spectrometry. Activity coefficients for phenyl salicylate have been calculated by means of the Wilson, NRTL, and UNIQUAC equations and with them were correlated solubility data that were compared with the experimental ones. The best correlation of the solubility data has been obtained by the Wilson equation by which the average root-mean-square deviation of temperature for the three systems is 1.03 K.